Atlantic Gandhi : the Mahatma overseas - Natarajan, Nalini (SAGE, 2013)
Atlantic Gandhi takes Mahatma Gandhi out of the national space of India and examines him as an ocean-faring diasporic cosmopolitan whose life reverberates with the revolutionary currents of the Atlantic rim.